2016
DOI: 10.1111/bcpt.12630
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol Induces Antinociceptive Effect in Mice Evaluated in Behavioural and Electrophysiological Models

Abstract: Geraniol (GER) is a monoterpene alcohol with various biochemical and pharmacological properties present in the essential oil of more than 160 species of herbs (especially the Cymbopogon genus). In this study, we evaluated the antinociceptive activity of GER in behavioural and electrophysiological in vitro experimental models of nociception using male Swiss mice. GER (12.5, 25 or 50 mg/kg i.p. and 50 or 200 mg/kg p.o.) reduced the number of writhes induced by acetic acid. The opioid antagonist naloxone (5 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…and 50-200 mg/kg, p.o.) were previously reported to possess significant antinociceptive activity in the writhing and glutamate tests in mice exploring antioxidant activity [29], as well as the inhibition of Na+ voltage-sensitive sodium channels [30], suggesting involvement in glutamatergic neurotransmission. No neurological alteration was produced by geranyl acetate, since motor performance was not modified in the rotarod test after at dosage of 200 mg/kg, i.p.…”
Section: Discussionmentioning
confidence: 99%
“…and 50-200 mg/kg, p.o.) were previously reported to possess significant antinociceptive activity in the writhing and glutamate tests in mice exploring antioxidant activity [29], as well as the inhibition of Na+ voltage-sensitive sodium channels [30], suggesting involvement in glutamatergic neurotransmission. No neurological alteration was produced by geranyl acetate, since motor performance was not modified in the rotarod test after at dosage of 200 mg/kg, i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Control mice were intranasally administered 50 μL of sterile phosphate-buffered saline (PBS). 24 h after inducing infection, the mice in the GOH groups were intraperitoneally injected with 12.5, 25, and 50 mg/kg GOH three times at 0, 6, 12 h. The doses of GOH used in the study were established based on previous studies [ 42 ] and our preliminary experiments. The mice were euthanized by CO 2 inhalation at 18 h (6 h after the last treatment with GOH), and the lung tissues were harvested and stored at -80 °C for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also indicated that geraniol, a monoterpene found in various flowers (rose (Rosa), lemon (Citrus limon), lavender (Lavandula angustifolia)) and fruits, and citronellal, which is a monoterpenoid with a strong lemon-like smell, stimulate glucagon-like peptide 1 secretion in mouse intestinal tissues and in cultured enteroendocrine cells [62]. In a study using mice, in which geraniol was intraperitoneally injected (thus, not through the digestive system) and responses to acetic acid were measured, geraniol was found to have as strong an analgesic impact as morphine, measured by the latency, to show writhing after intraperitoneal injection of acetic acid [77]. Oral treatment of geraniol in the same study did not produce as strong an impact as intraperitoneal injection of geraniol in the latency to show writhing, but the number of writhing events was less than the control group, which did not receive geraniol nor morphine treatment before injection of acetic acid [77].…”
Section: The Gut and Intestinementioning
confidence: 99%
“…In a study using mice, in which geraniol was intraperitoneally injected (thus, not through the digestive system) and responses to acetic acid were measured, geraniol was found to have as strong an analgesic impact as morphine, measured by the latency, to show writhing after intraperitoneal injection of acetic acid [77]. Oral treatment of geraniol in the same study did not produce as strong an impact as intraperitoneal injection of geraniol in the latency to show writhing, but the number of writhing events was less than the control group, which did not receive geraniol nor morphine treatment before injection of acetic acid [77]. In a separate study, orally administered geraniol was found to have an anti-depressant impact, measured by the immobility time in forced swimming tests and tail suspension tests [78].…”
Section: The Gut and Intestinementioning
confidence: 99%